Suzuki Tadashi's Intercultural Adaptations - Guertin, Caroline Aki Matsushita (Université d'Ottawa / University of Ottawa, 2015)
Contemporary theatre is increasingly visual, an aesthetic shift that has been analyzed in, among others, Hans-Thies Lehmann’s influential Postdramatic Theatre. This shift is apparent in Japanese director Tadashi Suzuki’s intercultural adaptations, which adapt plays of the Western repertoire for contemporary Japanese and international audiences in a style that is richly and evocatively visual. Notions drawn from postdramatic theatre, metatheatre and postcolonial theories are applied as framing devices to uncover the deep cultural and theatrical significance of Suzuki’s adaptive work. My approach to analyzing the three case studies: Suzuki’s King Lear, The Trojan Women, and Cyrano de Bergerac takes a more globalized view of theatrical adaptations that acknowledges the visual turn of contemporary theatre and contributes to the fields of intercultural performance studies and adaptation studies by expanding the notion of interculturalism beyond the limits imposed by current Western analytical perspectives.
Keywords: Suzuki Tadashi; Intercultural Theatre; Adaptation Studies; Japanese Contemporary Theatre; Asian Theatre; Theatre